Ответы и объяснения

  • ayka89
  • почетный грамотей
2011-10-08T17:21:40+00:00

-х - у + 6 = 0             -х - у = -6       

х + 2у - 3 = 0             х + 2у = 3      

                                    у = - 3

-х + 3 + 6 = 0

х = 9                Ответ(9; - 3)

 

 

6х + 3у + 18 = 0        6х + 3у = -18

8х - 3у - 24 = 0         8х - 3у = 24

                               14х      = 6

                                  х = 3/7

8 * 3/7  - 3у - 24 = 0

-3у =  144/7

х = -48/7

 

Ответ(- 48/7; 3/7)

 

4т - 2с = 10              -4т + 2с = -10

4т + 9с + 24 = 0        4т + 9с = -24

                                     11с = 34

                                     с = 34/11

4т - 2 * 34/11 = 10

4т = 178/11

т = 89/22

Ответ(34/11; 89/22)